R & UV Irradiation Methods to Improve the Efficacy of Silver Nanoparticles in the Eradication of Biofilm-Forming Microbes Isolated from Surfaces of Severe Accidental Wounds - Mohanty, Chirasmita; Das, Pratyush Kumar; Purohit, Gopal Krishna (International Journal of Scientific Research in Biological Sciences, 2022)
Bacterial biofilms are a major concern towards human health. Nanoparticles work against bacteria through a unique mechanism, making them a promising alternative for biofilm eradication. Silver nanoparticles are widely known and used for their efficient antibacterial property. In the current study, a swab sample was collected from the surfaces of 10-day-old wounds resulting from a road accident and cultured. Four biofilm-forming bacterial strains were isolated by studying the colony morphology and staining properties. Genomic characterization of the isolated strains was carried out by 16s rRNA sequencing using 27F and 149R universal primer. The fasta sequences were subjected to phylogenetic analysis following the maximum likelihood method using Mega software (Version 10.2.5). The biofilm-forming strains were identified as Escherichia coli (CMPD1), Klebsiella pneumonia (CMPD2), Pseudomonas aeruginosa (CMPD3), and Staphylococcus aureus (CMPD4). Silver nanoparticles were synthesized following the green synthesis approach for the anti-biofilm study using Cinnamomum tamala leaf extract as a natural reductant. 10 ml of different concentrations of silver nitrate (2 mM, 4 mM, 6 mM, 8mM, and 10mM) and plant extracts (1ml to 5 ml) were taken for the synthesis. The change in colour of the solution to dark brown confirmed the synthesis of silver nanoparticles. The absorption maxima of the nanoparticles obtained by using 4mM silver nitrate and 5 ml of leaf extract were found to be 430 nm using a UV-Vis spectrophotometer. Anti-microbial activity of the same sample showed higher inhibition efficiency as compared to others thereby confirming high concentrations of silver nanoparticles. The selected nanoparticle sample was divided into two parts. One part was irradiated with a 39W UV lamp (254 nm) and the other with a 100W IR lamp (1000 nm) for 10 minutes each. Post irradiation, the anti-biofilm assay was conducted in a 96-well microtiter plate. Irradiated nanoparticles showed higher anti-biofilm activity as compared to the non-irradiated ones. The activity of nanoparticles followed the sequence – IR>UV>Non-irradiated.